Efektivitas Layanan Pelindungan Pekerja Migran Di Dinas Ketenagakerjaan Dan Transmigrasi Kabupaten Sigi - Elzya M., Ananda; Daswati; Astuti, Agusta Sri (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to evaluate the extent to which the services provided by the Manpower and Transmigration Office of Sigi Regency can meet the needs and rights of migrant workers, in accordance with the mandate of Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers and also Regional Regulation Number 1 of 2022 concerning the Protection of Migrant Workers in Sigi Regency. This study uses the theory of Richard M Steers with 3 indicators, namely achievement of goals, integration, and adaptation. The method used in this study is a qualitative approach with a descriptive type, which collects data through interviews with related parties, including employees of the Manpower Office and registered and unregistered migrant workers. The results of the study indicate that despite efforts by the Manpower and Transmigration Office to provide comprehensive services, there are still a number of obstacles that affect the effectiveness of services, such as lack of human resources and inadequate budget. This study recommends improving coordination between various parties related to other government institutions and non-government institutions and strengthening information systems to improve accessibility of services for migrant workers. Thus, it is hoped that protection for migrant workers can be more optimal and in accordance with their needs, so as to reduce the risks faced during the migration process.